Simvastatin strongly reduces levels of Alzheimer's disease β-amyloid peptides Aβ42 and Aβ40 in vitro and in vivo - Faßbender, Klaus; Simons, M.; Bergmann, Carina; Stroick, Mark Gregor; Lütjohann, D.; Keller, P.; Runz, Heiko; Kühl, Sandra; Bertsch, Thomas; Bergmann, K. von; Hennerici, Michael G.; Beyreuther, Konrad; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2001)
Recent epidemiological studies show a strong reduction in the - incidence of Alzheimer's disease in patients treated with - cholesterol-lowering statins. Moreover, elevated Aβ42 levels and the - ɛ4 allele of the lipid-carrier apolipoprotein E are regarded as risk - factors for sporadic and familial Alzheimer's disease. Here we - demonstrate that the widely used cholesterol-lowering drugs simvastatin - and lovastatin reduce intracellular and extracellular levels of Aβ42 - and Aβ40 peptides in primary cultures of hippocampal neurons and - mixed cortical neurons. Likewise, guinea pigs treated with high doses - of simvastatin showed a strong and reversible reduction of cerebral - Aβ42 and Aβ40 levels in the cerebrospinal fluid and brain - homogenate. These results suggest that lipids are playing an important - role in the development of Alzheimer's disease. Lowered levels of - Aβ42 may provide the mechanism for the observed reduced incidence of - dementia in statin-treated patients and may open up avenues for - therapeutic interventions.
Gesehen am 31.03.2021